Ultrastructural correlates of ischaemic contracture during global subtotal ischaemia in the rat heart. - Harper, I. S. (1990)
The development of left ventricular ischaemic contracture and its correlation with ultrastructural and sarcolemmal permeability defects were studied in isolated rat hearts during global subtotal ischaemia. With acetate as substrate the hearts exhibited a rise in diastolic tension after 8-10 min at which time small foci of contracted myocytes were scattered throughout the myocardium. In hearts with 5% of the maximum diastolic tension (termed 5% contracture), the foci were situated predominantly in the subendocardium and papillary muscle. Contracted myocytes in these foci were capable of excluding ionic lanthanum thus demonstrating retention of normal sarcolemmal permeability properties. With 30% contracture ultrastructural damage had spread to the subepicardium and with further contracture there was an associated increase in the number and size of foci in all regions. In these foci, swelling of the tubular sarcolemmal system and occasionally of the sarcoplasmic reticulum appeared to precede myofibrillar contraction. At 50% contracture lanthanum influx into contracted cells became more frequent. Hearts developed full contracture by 15-18 min at which time most myocytes were contracted and retained lanthanum intracellularly. The heterogeneity of the response at a cellular level may offer a possible explanation for the lack of correlation between contracture and tissue ATP. A possible sequence of structural injury leading to impaired calcium homeostasis is also suggested.